Composite materials in concrete construction proceedings of the international seminar held at the University of Dundee, Scotland, UK on 5-6 September, 2002 - Dhir, Ravindra K.; Paine, Kevin A.; Newlands, Moray D. (Thomas Telford, 2002)
There is no substitute for concrete that can be used on the same engineering scale. Its sustainability, exploitation and further development are necessary for a healthy economy and environment worldwide. Concrete must keep evolving to satisfy the increasing demands of all its users.